Complications in the catheter ablation of atrial fibrillation: incidence and management - Takahashi, Atsushi; Kuwahara, Taishi; Takahashi, Yoshihide (Circulation journal : official journal of the Japanese Circulation Society, 2009)
Radiofrequency catheter ablation is widely performed as an effective treatment for recurrent, drug-resistant atrial fibrillation (AF). Recently, various types of ablation strategies, such as extensive encircling pulmonary vein (PV) isolation, linear ablation and complex fractionated electrogram-guided ablation, have been used to achieve a high efficacy for all types of AF. However, several complications (thromboembolic events, PV stenosis and atrio-esophageal fistula etc) with an incidence of 3.9-6%, have been reported. It is important to understand the incidence, prevention and management of complications in order to develop safe ablation strategies.